Exploration of student nurses' experiences in practice of patient safety events, reporting and patient involvement. (May 2021) - Morey, Sarah; Magnusson, Carin; Steven, Alison
Abstract: Background/introduction: Qualified and student nurses remain at the forefront of dealing with, and reporting, patient safety events or incidents. There has been limited exploration of whether and how the patient's perspective is represented by staff or student nurses using formal reporting systems. Objectives: The overall aim of the study was to explore the student nurses' experiences in practice of patient safety events they were themselves directly or indirectly involved in. This specifically explored the subsequent reporting and inclusion of the patient perspectives that may or may not have taken place. Design: A qualitative approach to this research was selected using the principles of thematic analysis to analyse data gathered from focus groups of student nurses across all year groups. Setting: Three universities participated in the study located in the north east, south east and east of England. Participants: Student nurses from across the year groups attended focus groups. Methods: Following ethical approval and informed consent, participants took part in focus groups within each university setting. Data were transcribed verbatim and analysed using thematic analysis. Results: Three themes were identified: the benefit of reporting and patient involvement, the barriers experienced by the students in reporting and the support needed to ensure they do the right thing in practice. Conclusion: Learning for students from patient safety incidents is important and seeking patients' views and perceptions adds to the learning experience. There are however challenges for the student in practice in both reporting and patient involvement. Resources are needed that follow and feed into the student learning alongside a workforce that see the benefit of learning from those we care for.